2014
DOI: 10.1177/2372732214548677
|View full text |Cite
|
Sign up to set email alerts
|

Designing Classrooms to Maximize Student Achievement

Abstract: Improving student achievement is vital for our nation’s competitiveness. Scientific research shows how the physical classroom environment influences student achievement. Two findings are key: First, the building’s structural facilities profoundly influence learning. Inadequate lighting, noise, low air quality, and deficient heating in the classroom are significantly related to worse student achievement. Over half of U.S. schools have inadequate structural facilities, and students of color and lower income stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
91
0
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(107 citation statements)
references
References 37 publications
3
91
0
13
Order By: Relevance
“…The ideal classrooms were described as ventilated spaces with the necessary lighting for the daily activities, which is in line with the description given by participants of previous studies (Tanner, 2008). Furthermore, the participants of the present study indicated the need for visual resources in the schools, such as guiding posters and pictograms (Cheryan, Ziegler, Plaut, & Meltzoff, 2014;Gaines & Curry, 2011).…”
supporting
confidence: 81%
“…The ideal classrooms were described as ventilated spaces with the necessary lighting for the daily activities, which is in line with the description given by participants of previous studies (Tanner, 2008). Furthermore, the participants of the present study indicated the need for visual resources in the schools, such as guiding posters and pictograms (Cheryan, Ziegler, Plaut, & Meltzoff, 2014;Gaines & Curry, 2011).…”
supporting
confidence: 81%
“…Furthermore, students who have more self-relevant role models, brought about because of increased diversity, experience increased long-term positive consequences, such as decreased implicit stereotypical beliefs, future job security, and enhanced well-being (Brady, Cohen, Jarvis, & Walton, 2017;Dasgupta & Asgari, 2004). Changing the cues in the environment-especially in some of the smaller ways, like changing whose pictures are on the walls-can have substantial payoffs for marginalized group members (see Cheryan, Ziegler, Plaut, & Meltzoff, 2014).…”
Section: Recommendation 1: Be Mindful Of Cues That Signal Inclusion (mentioning
confidence: 99%
“…Working in warm environments led to a lower performance than in thermos-neutral rooms [35,36]. In addition to calibrating the temperature, ventilation involves oxygen renewal, and exposure to poor air quality decreases student attention and entails passive social behaviour [37]. Manual window-airing is the usual method of ventilation in most Spanish educational buildings, and, in Portugal, this method under monitoring has provided appropriate ventilation for a quarter of the academic year [38].…”
mentioning
confidence: 99%